Sustainable Accounting for Companies in Indonesia’s UNESCO Global Geopark Regions - Kholis, Azizul; Darma, Jufri; Fatah Hassanudin, Adbul; Prayogi, Wanda (Department of Accounting, Faculty of Economics & Business, 2026)
The study aims to analyze the role of sustainable accounting in strengthening the corporate image of companies operating in UNESCO Global Geopark (UGGp) areas in Indonesia, by considering corporate social performance and geopark programs as mediating mechanisms. Sustainable accounting in this study encompasses economic, social, and environmental aspects disclosed and reported in accordance with the Global Reporting Initiative and accounting standards applicable in Indonesia. The study is grounded in Stakeholder Theory and Corporate Social Performance, employing a pentahelix approach to capture the complexity of relationships between companies and stakeholders in geopark areas. Research data collected through a survey of 119 company executives operating across 12 UNESCO Global Geoparks in Indonesia and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that the geopark pillar, comprising education, conservation, and community empowerment activities, has a positive effect on corporate social performance and corporate image. Furthermore, corporate social performance and corporate image are shown to play a significant role in encouraging the adoption of sustainable accounting. The disclosure and reporting of sustainable accounting practices also strengthen these relationships, underscoring the importance of transparency in corporate sustainability practices. The contribution of this study lies in enriching the literature on sustainable accounting within conservation-based contexts by demonstrating that geopark programs function as strategic mechanisms linking social performance, corporate image, and the internalization of sustainable accounting in support of sustainable development in Indonesia (;)